Benefits of crop diversification in Fiji's sugarcane farming. Issue 1 (1st January 2020) - Singh, Amar
Abstract: The sugar industry has shaped the development of Fiji's economy for over a century; but, for the past 15 years, sugarcane production has been declining. A study was undertaken of over 300 sugarcane farmers in Fiji to determine the benefits of crop diversification and to compare the level of profitability for farmers fully dedicated to sugarcane farming and sugarcane farmers who have diversified. The findings demonstrate that a farmer in the latter group was able to achieve 45% higher profitability than one in the former. Fiji has the potential to increase farm output from diversification, but the relevant stakeholders need to help farmers secure markets and provide appropriate guidance and training.